Developing an Impartial Game by Mathematical Approach. Issue 1 (May 2020) - Mohd Zain, Azlan; Abdul Rahman, Afiq; Hawani Haris Fadzillah, Nurhafiyah; Rusdi, Aimi; Najwa Anuar Rosdi, Ainur; Amin Izam Hasri, Muhammad
Abstract: In this study, we developed an impartial game namely Nim by using a mathematical approach. The game consists of multiple ways of movement for player winning the game. A total of five players participating in the game testing. The experiment shows that the proposed impartial game for learning process is easy to use.